Executive Committee Minutes 2017-10-19 - Academic Senate:::::::::
Agenda – Approved. Minutes of 10/5/17 – delayed. Chair Report. Provost Report. WASC Visit. EPC Report. APARC Report. CFA Report. Senate agenda – Approved.